2007
DOI: 10.1590/s0074-02762007000800014
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro model for dengue virus infection that exhibits human monocyte infection, multiple cytokine production and dexamethasone immunomodulation

Abstract: An important cytokine role in dengue fever pathogenesis has been described. These molecules can be associated with haemorrhagic manifestations, coagulation disorders, hypotension and shock, all symptoms implicated in vascular permeability and disease worsening conditions. Several immunological diseases have been treated by cytokine modulation and dexamethasone is utilized clinically to treat pathologies with inflammatory and autoimmune ethiologies. We established an in vitro model with human monocytes infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…In our in vitro infection model, we observed markedly higher TNF-α production after infection with pathogenic virus (DENV2) as compared to the non-pathogenic viruses (YF17DD and YF17D/DENV2), providing further evidence that this cytokine plays a role in flavivirus immunopathogenesis. Other authors have also observed TNF-α production in DC or monocyte cultures in the presence of DENV2 and some authors even associate it with the infected cell (Hacker et al 1998, Querec et al 2006, Deauvieau et al 2007, Reis et al 2007, Ahmad et al 2008, Nightingale et al 2008, Levy et al 2009. A moderate level of TNF-α production may be beneficial to mature cells that may become good antigen presenters.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In our in vitro infection model, we observed markedly higher TNF-α production after infection with pathogenic virus (DENV2) as compared to the non-pathogenic viruses (YF17DD and YF17D/DENV2), providing further evidence that this cytokine plays a role in flavivirus immunopathogenesis. Other authors have also observed TNF-α production in DC or monocyte cultures in the presence of DENV2 and some authors even associate it with the infected cell (Hacker et al 1998, Querec et al 2006, Deauvieau et al 2007, Reis et al 2007, Ahmad et al 2008, Nightingale et al 2008, Levy et al 2009. A moderate level of TNF-α production may be beneficial to mature cells that may become good antigen presenters.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, DCs have a crucial role in initiating host defence mechanisms; through antigen presentation and cytokine production, they can define the fate of the immunological response (Blanco et al 2008). Both DENV and YF vaccine viruses are known to infect DCs and monocytes in vitro (Wu et al 2000, Barba-Spaeth et al 2005, Reis et al 2007). We aimed to characterise the similarities and differences between flavivirus infections with distinct virulence patterns that elicit long lasting in vivo immunity (Monath 2001, Halstead 2007.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Monocytes and T lymphocytes are activated during human infection, producing several pro-inflammatory mediators and may have amplified activation during secondary infection to become sources of intense cytokine production. Several investigations have followed patients during acute infection to monitor their plasma cytokine content and found that TNF-α is among the first detected cytokines in patients as well as in peripheral blood mononuclear cell (PBMC) cultures (Bethell et al 1998, Braga et al 2001, Reis et al 2007). In general, these mediators may promote platelet and endothelial activation, culminating in thrombocytopenia, vascular permeability, hypotension and shock, as observed in severe cases of dengue (Fink et al 2006).…”
Section: Monocytes/macrophages Are Important Targets For Dengue Virusmentioning
confidence: 99%